2005
DOI: 10.3748/wjg.v11.i12.1769
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric side effects of pegylated interferon alfa-2b as compared to conventional interferon alfa-2b in patients with chronic hepatitis C

Abstract: Our findings suggest that the extent and frequency of depressive symptoms in total are not reduced by peginterferon. Monitoring and management of neuropsychiatric toxicity especially depression have to be considered as much as in antiviral therapy with unmodified interferon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 25 publications
1
35
0
1
Order By: Relevance
“…Therefore, it is not possible to extrapolate to other patient groups. However, from small studies there seems no difference in the development or the mechanism of depression in other patient groups [9,30] . Secondly, although larger than previous studies [9] our sample size is still relatively low resulting in large confidence intervals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is not possible to extrapolate to other patient groups. However, from small studies there seems no difference in the development or the mechanism of depression in other patient groups [9,30] . Secondly, although larger than previous studies [9] our sample size is still relatively low resulting in large confidence intervals.…”
Section: Discussionmentioning
confidence: 99%
“…Although depressive symptomatolog y occurring in patients treated with interferon has usually been called 'depression' or 'major depressive episode', the more appropriate ter m according to new DSM-Ⅳ -TR should be 'substance induced mood disorder'. There are psychopathological (e.g., more irritability) [27] , epidemiological (the gender difference in major depressive episode is different from the gender difference in interferon induced mood disorder) [28] , genetic [29] and treatment (more patients than in major depressive episode respond well to SSRIs) [30] arguments to support this really to be a different disorder. This study has some limitations.…”
Section: Discussionmentioning
confidence: 99%
“…12,19 Nevertheless, only a few studies have prospectively assessed the frequency and time-course of depressive syndromes during treatment with PegIFN and RBV using validated psychiatric assessment tools, and anxiety syndromes have been analysed. 18,20 Several studies and case reports have shown that antidepressants, especially selective serotonin reuptake inhibitors (SSRI), are useful in ameliorating IFN-induced depression. [21][22][23] Furthermore, it has been suggested that antidepressants can also prevent psychiatric adverse effects in patients with melanoma treated with IFN 24 as well as in patients with hepatitis C. 25 Two recent studies showed that SSRI treatment cannot prevent induceddepressive episodes but can ameliorate the symptomatology.…”
Section: Backgroundsmentioning
confidence: 99%
“…30 Additionally, use of Peg-IFNα-2b has been associated with better quality of life compared to the use of standard IFNα-2b. 31 While one study showed that depression, hostility, and anger did not decrease significantly with the use of Peg-IFNs, 32 another trial demonstrated that patients treated with Peg-IFNα-2a at a standard dose of 180 µg per week plus ribavirin had significantly less depression compared to those treated with standard IFN plus ribavirin and had delayed presentation of depressive symptoms, occurring usually after the week 12 of therapy. 33 Manns et al demonstrated that the use of Peg-IFNα-2a plus ribavirin was associated with similar frequency of adverse events compared to standard IFN plus ribavirin (31% depression, 35% irritable behavior, and 40% sleep disturbances).…”
Section: Introductionmentioning
confidence: 99%